Early marriage and its impact on children's Islamic religious education in the family - Jaelani (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Many young couples struggle with parenting responsibilities due to lack of education, emotional maturity, and financial stability, impacting their ability to provide adequate Islamic religious education for their children. This study examines how early marriage influences children's Islamic education in the aspects of Qur’anic education, faith, worship, and morals. Methods: This study employs qualitative field research methods, utilizing both primary and secondary data sources. Data collection was conducted through observations, interviews, and document analysis. Findings: The research findings indicate that early marriage significantly affects children's Islamic religious education, particularly in four key areas: Qur’anic studies, faith, worship, and moral development. Due to young parents' lack of knowledge and understanding, religious education is often delegated to external figures such as ustadz (religious teachers), or institutions like Qur’anic learning center and madrasah diniyah. Additional factors such as parents' busy schedules, technological advancements, and environmental influences further contribute to the low quality of Islamic education in these families. Furthermore, emotional instability among young couples also affects their children's overall development. Conclusion: The study concludes that early marriage negatively impacts the quality of children's Islamic education. Young parents lack the necessary skills and knowledge to provide proper religious education, leading to heavy reliance on external institutions. The findings highlight the need for educational programs, parental guidance, and community-based initiatives to support young families in improving their children's religious education. Novelty/Originality of this article: This study provides a unique insight into the relationship between early marriage and children's Islamic education in rural Indonesia. The findings serve as a valuable resource for educators, religious leaders, and policymakers in addressing the challenges posed by early marriage in traditional communities.